2019
DOI: 10.3390/molecules24224114
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Behavior of Oligo(Ethylene Glycol) Dendrons Spread Alone and in Combination with a Phospholipid as Langmuir Monolayers at the Air/Water Interface

Abstract: Dendrons consisting of two phosphonate functions and three oligo(ethylene glycol) (OEG) chains grafted on a central phenoxyethylcarbamoylphenoxy group were synthesized and investigated as Langmuir monolayers at the surface of water. The OEG chain in the para position was grafted with a t-Bu end-group, a hydrocarbon chain, or a partially fluorinated chain. These dendrons are models of structurally related OEG dendrons that were found to significantly improve the stability of aqueous dispersions of iron oxide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Nontypical amphiphiles include polymers, carbonaceous compounds (carbon nanotubes and graphene), silica, other inorganic and organic−inorganic hybrid materials. Examples of inorganic and organic−inorganic materials are macrocyclic molecules, 260−265 dendrimers, 266,267 silica, 268−271 carbon-based particles, 272 black phosphorus, 273 clay nanosheets, 274 magnetic soft spheres, 275 gold nanoparticles, 276 CdS nanoparticles/quantum dots, 277,278 ionic liquids, 279−282 diureasil hybrid compounds, 283,284 and inorganic nanowires. 285 Since Sections 6 and 7 will cover considerable work on LB films of nontypical amphiphiles, in this section, we restrict ourselves to providing a general discussion of the challenges and opportunities in producing such Langmuir and LB films.…”
Section: Langmuir and Lb Films Of Nontypicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Nontypical amphiphiles include polymers, carbonaceous compounds (carbon nanotubes and graphene), silica, other inorganic and organic−inorganic hybrid materials. Examples of inorganic and organic−inorganic materials are macrocyclic molecules, 260−265 dendrimers, 266,267 silica, 268−271 carbon-based particles, 272 black phosphorus, 273 clay nanosheets, 274 magnetic soft spheres, 275 gold nanoparticles, 276 CdS nanoparticles/quantum dots, 277,278 ionic liquids, 279−282 diureasil hybrid compounds, 283,284 and inorganic nanowires. 285 Since Sections 6 and 7 will cover considerable work on LB films of nontypical amphiphiles, in this section, we restrict ourselves to providing a general discussion of the challenges and opportunities in producing such Langmuir and LB films.…”
Section: Langmuir and Lb Films Of Nontypicalmentioning
confidence: 99%
“…Nontypical amphiphiles include polymers, carbonaceous compounds (carbon nanotubes and graphene), silica, other inorganic and organic–inorganic hybrid materials. Examples of inorganic and organic–inorganic materials are macrocyclic molecules, dendrimers, , silica, carbon-based particles, black phosphorus, clay nanosheets, magnetic soft spheres, gold nanoparticles, CdS nanoparticles/quantum dots, , ionic liquids, diureasil hybrid compounds, , and inorganic nanowires …”
Section: Langmuir and Lb Films Of Nontypical Amphiphilesmentioning
confidence: 99%
“…Subsequent decantation of non‐gelated THF or cold filtration led to highly pure ASP‐1 , which is amphiphilic based on its hydrophobic/hydrophilic substituents. Importantly, hydrophilic oligoethylene glycol units are essentially dissolved in the water subphase when spread at an air–water interface [ 31 ] while the hydrophobic alkoxy‐substituted group is repelled away from the water subphase. This provides a strong basis for the assembly of the molecules especially where a lateral force can be applied to manipulate the molecular spacing in situ.…”
Section: Resultsmentioning
confidence: 99%
“…These structures could be similar to the ones found for monolayers of poly­(methylmethacrylate) in which at the interface, polymer coils adopt a soft-disk (pancake) shape; this behavior was associated with a fluid-to-soft-glass transition as the polymer concentration increases above a critical packing fraction at a constant temperature . Other authors have related the different phases observed in the isotherms with conformational transitions observed for deblock copolymers (e.g., poly­(styrene)-poly­(ethylene oxide). , We present amplitude AFM images for the PSMA photo-polymerized films as they allowed us to better highlight the surface morphological and structural differences of the films due to different irradiation times (See Supporting Information). Figure c shows the AFM image of the PSMA 180 LB film.…”
Section: Results and Discussionmentioning
confidence: 99%
“…39 Other authors have related the different phases observed in the isotherms with conformational transitions observed for deblock copolymers (e.g., poly-(styrene)-poly(ethylene oxide). 34,40 We present amplitude AFM images for the PSMA photo-polymerized films as they allowed us to better highlight the surface morphological and structural differences of the films due to different irradiation times (See Supporting Information). Figure 4c shows the AFM image of the PSMA 180 LB film.…”
Section: Characterization Of Monolayermentioning
confidence: 99%